2011
DOI: 10.1615/jlongtermeffmedimplants.v21.i2.50
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure in Orthopaedic Surgery

Abstract: Orthopaedic diseases affect a broad spectrum of patients, and many of these have concomitant medical problems that may differ from those of the general surgical population. Acute postoperative renal failure is thought to arise secondary to acute tubular necrosis from volume depletion, reduction in glomerular filtration rate, hypotension, and nephrotoxic drugs. If acute renal failure occurs and necessitates hemodialysis, morbidity and mortality are significantly increased. To enhance the literature, we performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…Our results are consistent with other previously published reports on this subject [4,30,38] finding an increase in postoperative kidney injury with multiple antibiotic prophylaxis. Furthermore, our data also show the effect that hip and knee arthroplasty can have on patients.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are consistent with other previously published reports on this subject [4,30,38] finding an increase in postoperative kidney injury with multiple antibiotic prophylaxis. Furthermore, our data also show the effect that hip and knee arthroplasty can have on patients.…”
Section: Discussionsupporting
confidence: 94%
“…We also found higher ASA classification and preoperative kidney disease to be independent predictors of AKI postoperatively consistent with prior literature, which reports that medical comorbidities and preoperative kidney function can lead to kidney injury after orthopaedic surgery [30]. Jafari et al [18] found that preoperative kidney disease and medical comorbidities predisposed patients to developing AKI after primary TJA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, major abdominal surgery can cause an increase of intra-abdominal pressure, linked to an increase in capillary permeability and interstitial fluid accumulation or to a diminished abdominal wall compliance that, in turn, causes intrarenal vascular congestion with a reduction in renal perfusion [83]. On the other side, orthopedic patients include often very aged people with severe co-morbidities (i.e., hypertension, renal failure, diabetes) that easily expose them to an increased risk of postoperative AKI [93]. Recent findings suggest that advanced age, hypertension, general anesthesia, and low intraoperative arterial pressure are all risk factors for AKI after joint replacement surgery [94].…”
Section: Discussionmentioning
confidence: 99%
“…The HTO group showed significantly low infection rate, which may be related to a relatively short operation time [ 22 24 ] and showed low risk of DVT possibly due to routine usage of mechanical compression after surgery [ 25 ], and pharmacologic prophylaxis [ 26 ]. There have been previous studies on factors related to ARF after orthopedic surgery, but studies related to different surgical methods, especially artificial joint surgery, have been insufficient and may require further evaluation [ 27 , 28 ]. On the other hand, cemented knee arthroplasty, as one of the independent risk factors for postoperative ICU admission in some studies could relate that the result of higher ICU admission in UKA as shown in Table 4 [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%